Construction of nucleus-directed fluorescent reporter systems and its application to verification of heterokaryon formation in Morchella importuna - Zhang, Qianqian; Shu, Fang; Chen, Xin; Liu, Wei; Bian, Yinbing; Kang, Heng (Frontiers in Microbiology, 2022)
Morchella importuna (M. importuna) is a rare fungus with high nutrition value and distinct flavor. Despite the successful artificial cultivation, its genetic characteristics and biological processes such as life cycle, reproductive system, and trophic mode remain poorly understood. Considering this, we constructed pEH2B and pMH2B vectors by fusing M. importuna endogenous histone protein H2B with fluorescent proteins eGFP or mCherry, respectively. Based on the constructed pEH2B and pMH2B vectors, nuclear fluorescence localization was performed via Agrobacterium tumefaciens-mediated transformation (ATMT). These two vectors were both driven by two endogenous promoters glyceraldehyde 3-phosphate dehydrogenase (GPD) and ubiquitin (UBI). The vector-based reporter systems were tested by the paired culture of two genetically modified strains pEH2B-labeled M04M24 (24e, MAT1-1-1) and pMH2B-abeled M04M26 (26m, MAT1-2-1). The fluorescence observation and molecular identification results indicated the successful hyphal fusion and heterokaryon formation. We found that the expression of the reporter genes was stable, and it did not interfere with the growth of the fungus. Our constructed nucleus-directed fluorescent systems in M. importuna can be used for monitoring the dynamic development and reproductive processes in living cells and also for monitoring the interaction between morels and plant roots. Therefore, morels exhibit the potential to be a candidate organism used for the research on basic biology and genetics of ascomycetes.